(untitled) (Journal of Hama University, 2024)
Introduction: Health organizations face many challenges resulting from the rapid developments and the multiplicity of means of communication, which in turn cause various pressures on the workers, affecting negatively and directly the human resources within the organization, in addition to the large costs resulting from them. Study Objective: The study aimed to determine the level of emotional intelligence and to know the strategy of coping with work pressures among nursing staff in Tishreen University Hospital in Lattakia.Research Materials and Methods: A descriptive analytical study was conducted on an appropriate sample of (200) nurses working in Tishreen University Hospital, working during the data collection period (the available sample). The researcher relied on a questionnaire to assess self-management emotional intelligence developed by (Schutte et.al, 1998), and a questionnaire to assess strategies for coping with work stress, which was used by Al-Shawi (2010) in his research on coping strategies and their relationship to psychological stress to collect data related to the study, and after unpacking The data were statistically processed and tabulated using the SPSS statistical program version (20) .Results: The results of the current study showed that the level of emotional intelligence of the nursing staff (study sample) as a whole was medium, and the level of using strategies to cope with work stress for the nursing staff (study sample) as a whole was medium, with a strong and statistically significant relationship between emotional intelligence And the use of coping strategies for work stress.Conclusion and Recommendations: Emotional intelligence is considered one of the most important psychological factors that nurses must have in order to practice their work in a healthy manner, hospital managers were recommended to assess the emotional intelligence of nurses, encourage them to use positive work stress coping strategies, and conduct induction courses.